2015
DOI: 10.1093/pcp/pcv160
|View full text |Cite
|
Sign up to set email alerts
|

A Cyan Fluorescent Reporter Expressed from the Chloroplast Genome ofMarchantia polymorpha

Abstract: Recently, the liverwort Marchantia polymorpha has received increasing attention as a basal plant model for multicellular studies. Its ease of handling, well-characterized plastome and proven protocols for biolistic plastid transformation qualify M. polymorpha as an attractive platform to study the evolution of chloroplasts during the transition from water to land. In addition, chloroplasts of M. polymorpha provide a convenient test-bed for the characterization of genetic elements involved in plastid gene expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…In the blue/cyan range, mTurquoise2 was chosen for its very low p K a (p K a mTurquoise2 = 3.1), which was the lowest of all proteins tested in this study (Goedhart et al., ). Despite being a relatively new FP, it has been successfully expressed in several plant species such as A. thaliana , N. benthamiana, and Marchantia polymorpha (Boehm, Ueda, Nishimura, Shikanai, & Haseloff, ; Ghareeb, Laukamm, & Lipka, ; Rolland, Badger, & Price, ).…”
Section: Resultsmentioning
confidence: 99%
“…In the blue/cyan range, mTurquoise2 was chosen for its very low p K a (p K a mTurquoise2 = 3.1), which was the lowest of all proteins tested in this study (Goedhart et al., ). Despite being a relatively new FP, it has been successfully expressed in several plant species such as A. thaliana , N. benthamiana, and Marchantia polymorpha (Boehm, Ueda, Nishimura, Shikanai, & Haseloff, ; Ghareeb, Laukamm, & Lipka, ; Rolland, Badger, & Price, ).…”
Section: Resultsmentioning
confidence: 99%
“…This approach was recently extended to the expression of a fluorescent reporter gene from the Marchantia plastome (Boehm et al 2016), which allows characterization of plastid promoters in this model system (see Fig. 3).…”
Section: Synthetic Botanymentioning
confidence: 99%
“…In vitro assays of inserted genes with several synonymous codons show that translation efficiency does not always correlate with codon usage in plastid mRNAs (Nakamura and Sugiura, 2007), but they have been used in several codon optimization studies (Lutz et al, 2001;Ye et al, 2001;Franklin et al, 2002;Lenzi et al, 2008;Jabeen at al., 2010;Madesis et al, 2010;Gisby et al, 2011;Wang et al, 2015b;Boehm et al, 2016;Nakamura et al, 2016). While some studies achieved significant increases in expression (75-to 80-fold) after codon optimization (Franklin et al, 2002;Gisby et al, 2011), other studies observed negligible enhancement (Ye et al, 2001;Lenzi et al, 2008;Daniell et al, 2009;Wang et al, 2015b;Nakamura et al, 2016).…”
mentioning
confidence: 99%